Climate ambition and COVID-19 - Positive Energy; Nanos Research (Université d'Ottawa | University of Ottawa, 2020)
This (telephone and online) survey gauged views of 1000 Canadians on energy issues, including climate change and the necessary ambition of mitigation policies. The survey suggests that Canadians are still likelier to say this is the best rather than the worst time to be ambitious about climate change.
Keywords: Canada; Public Opinion; Climate Change; Energy Policy; Covid -19; Renewables; Surveys